Analisis Visualisasi Data untuk Mendukung Pengambilan Keputusan Bisnis pada UMKM Sajisaja Menggunakan Tableau - Anjara, Febria (Indo Publishing, 2025)
This study aims to analyze the sales data of UMKM Sajisaja by utilizing data visualization through Tableau. UMKM Sajisaja is a culinary micro-enterprise offering several main dishes, including Ayam Cabe Garam, Ayam Woku, Ayam Cabe Ijo, and Salad. One of the main challenges faced by the enterprise is the limited ability to process sales data, which makes it difficult to identify trends, best-selling products, customer segmentation, and daily sales patterns that are essential for strategic decision-making. The research method applied was a quantitative descriptive approach by collecting monthly and daily sales data, along with customer segmentation, within the period of January–June 2024. The data were processed and visualized using Tableau, resulting in insights into monthly sales trends, product distribution, customer segmentation, and daily sales performance. The findings reveal a consistent increase in sales from January to May 2024, with peak sales recorded in May at 480 portions. The best-selling product was Ayam Cabe Garam, contributing 35% of total sales. Customer segmentation indicated that students made up the largest share at 55%, followed by workers at 30%, and housewives at 15%. Daily sales patterns showed the highest transactions occurred on Fridays and Saturdays. These results demonstrate that Tableau-based visualization provides clearer and more accessible information, enabling UMKM Sajisaja to develop more effective marketing strategies, optimize product management, and enhance customer service